KEKERASAN DALAM RUMAH TANGGA; SUATU TINJAUAN INTERAKSIONIS - Fakhri Usmita (UIR PRESS, 2017)
Domestic violence that is unique violence, especially cause offender and the victim are closely or have a bond. Using literature review especially with symbolic interactionist approach, this article would like to explain simply why someone who is